Edukasi Pengelolaan Sampah Rumah Tangga Dalam Kesadaran Lingkungan Pembangunan Berkelanjutan bagi warga Klapanunggal Bogor - Eka Rista Harimurti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This community service activity aims to raise environmental awareness among residents of Klapanunggal, Bogor, through education on household waste management from a sustainable development perspective. The Participatory Action Research (PAR) method was implemented through planning, action, observation, and reflection, actively involving the community in each stage of the activity. Education was delivered through material delivery, participatory discussions, and hands-on practice of sorting and processing household waste. The results of the activity indicate an increase in public knowledge and awareness regarding the importance of environmentally friendly waste management, reflected in changes in residents' attitudes and behaviors regarding waste sorting, reducing littering, and beginning to utilize organic waste productively. This activity also had a positive impact on the cleanliness of residential areas and supported sustainable development efforts at the local level. Therefore, participatory household waste management education can be an effective strategy for building sustainable environmental awareness.